Host specificity in the host-seeking larva of the dipteran parasitoid Mallophora ruficauda and the influence of age on parasitism decisions - Barrantes, María Eugenia (2014)
Larvae of the robber fly Mallophora ruficauda are ectoparasitoids of white grubs and adults are an important apiculture pest in Argentina. Females oviposit on tall grasses and the second instar larva actively searches and locates hosts. There are nine potential hosts in the distribution area of this parasitoid and Cyclocephala signaticollis (Coleoptera: Scarabaeidae) is the most parasitized in the field. However, M. ruficauda has a certain degree of behavioural flexibility towards different host species, and not being a strict specialist. The conditions under which the parasitoid orientates and accepts different hosts' species are unknown. We studied the host specificity of M. ruficauda towards three species of Cyclocephala genus and we determined whether this specificity depends on larval age. We also evaluated whether larva orientation towards Cyclocephala species changes with chemical cue concentration. We assessed host specificity measuring the orientation and acceptance behaviours towards kairomones extracts and live individuals of Cyclocephala species using M. ruficauda larvae of low and high life expectancy (i.e., young and aged second instar larvae). We observed that young larvae orientated only towards C. signaticollis chemical stimulus, whereas aged larvae orientated also towards C. modesta, and the same was observed with increasing stimuli's concentration. Both young and aged M. ruficauda larvae orientate towards live C. signaticollis and C. putrida species and rejected C. modesta. Also, we found that larvae accepted all Cyclocephala hosts. In conclusion, our results indicate that specificity in the laboratory, observed through host orientation and host acceptance behaviours, depends not only on the availability of host species, but also on the nature of the host's stimuli combined with parasitoid age.